Studi Biologi Ulat Bulu Lymantria marginata Wlk. (Lepidoptera : Lymantridae) Pada Tanaman Mangga - DARMIATI, NI NENGAH; SUSILA, WAYAN; ASTRIYANI, NI KADEK NITA KARLINA ASTRIYANI (Agrotrop : Journal on Agriculture Science, 2014)
The study was conducted at the Laboratory of Plant Pest and Disease Management, Department of Agroecotechnology, Faculty of Agriculture, University of Udayana. The purpose of this study was to determine the life cycle of caterpillars L. marginata, praoviposisi period, oviposition, pascaoviposisi, male imago long life, female imago long life and fecundity of caterpillars L. marginata and sex ratio of caterpillars L. marginata The results showed that the life cycle of L. marginata average of 52.00 ± 3.68 days with an egg stage was 8.20 ± 1.88 days, larval stage average 29.05 ± 1.76 days, and the pupal stage an average of 12.60 ± 2.18 days (n = 20). The number of eggs laid by the female imago is 2872 grains with an average 143.60 ± 34.63 eggs per imago, with praoviposisi period was 2.15 ± 0.75 days, oviposition period of 1.80 ± 0.77 days, a period pascaoviposisi 2.05 ± 0.83 days. Females imago long live ranged from 5-7 days with an average of 6 ± 0.85 days and males imago long life ranged from 2-7 days with an average of 4.5 ± 1.54 days (n = 20). Sex ratio of L. marginata approaching 1:1 (47% males and 53% females
Keywords: Biology, caterpillars L. marginata, Mango Plant (Mangifera indica)